1996
DOI: 10.1182/blood.v87.5.1754.bloodjournal8751754
|View full text |Cite
|
Sign up to set email alerts
|

A bicistronic therapeutic retroviral vector enables sorting of transduced CD34+ cells and corrects the enzyme deficiency in cells from Gaucher patients

Abstract: Corrective gene transfer for therapeutic intervention in metabolic and hematopoietic disorders has been hampered by the relatively inefficient transduction of human hematopoietic stem cells. To overcome this, a bicistronic recombinant retrovirus has been generated that delivers both a therapeutic glucocerebrosidase (GC) cDNA for the treatment of Gaucher disease, and a small murine cell surface antigen (heat-stable antigen [HSA]) as a selectable marker. An amphotropic retroviral- producing cell clone was create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Fluorometric enzyme assays were modified from previously described methods (Medin et al , 1996a , 1996b ; Okumiya et al , 2006 ; Bedia et al , 2010 ). Substrates used for α‐gal A, GCase, and GAA activities were 5 mM 4‐methylumbelliferyl‐α‐ d ‐galactopyranoside (Sigma‐Aldrich M7633), 15 mM 4‐methylumbelliferyl‐β‐ d ‐glucopyranoside (Sigma‐Aldrich M3633), and 1.5 mM 4‐methylumbelliferyl‐α‐ d ‐glucopyranoside (Sigma‐Aldrich M9766), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorometric enzyme assays were modified from previously described methods (Medin et al , 1996a , 1996b ; Okumiya et al , 2006 ; Bedia et al , 2010 ). Substrates used for α‐gal A, GCase, and GAA activities were 5 mM 4‐methylumbelliferyl‐α‐ d ‐galactopyranoside (Sigma‐Aldrich M7633), 15 mM 4‐methylumbelliferyl‐β‐ d ‐glucopyranoside (Sigma‐Aldrich M3633), and 1.5 mM 4‐methylumbelliferyl‐α‐ d ‐glucopyranoside (Sigma‐Aldrich M9766), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a recent report shows 8% of infection of positively selected CD34 + cells, a value identical to the one reported here ( Limon et al , 1997 ). Finally, B cells have been studied so far only using in vitro immortalized EBV‐LCL lines and, in the few reports available, normal HUVEC have shown much lower levels of infection ( Bauer & Miller, 1995; Candotti et al , 1996 ; Hacein‐Bey et al , 1996 ; Medin et al , 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EGFP gene has already been used in murine bone marrow ( Persons et al , 1997 ) and human cord blood cells ( Verhasselt et al , 1998 ) and shown not to interfere with their in vitro and in vivo differentiating capacity ( Persons et al , 1997 ; Bierhuizen et al , 1997 ; Verhasselt et al , 1998 ). Others have reported alternative selection procedures based on the introduction of membrane proteins ( Bonini et al , 1997 ; Phillips et al , 1996 ; Garcia‐Hernandez et al , 1997 ; Medin et al , 1996 ; Conneally et al , 1996 ; Champseix et al , 1996 ; Su et al , 1997 ). It will be important to test the same vector used here with similar surface markers in order to allow rapid selection of large numbers of infected cells by affinity columns procedures more clinically acceptable than FACS sorting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane antigens have also been investigated as potential in vitro selectable markers. Thus CD24 8, 9, murine heat shock antigen 10, 11 and a truncated version of the nerve growth factor receptor 12 have all been used, along with either FACS or magnetic bead isolation to provide enriched populations of gene‐modified cells. In a similar way, vectors encoding the green fluorescent protein (GFP) or one of its derivatives may also be used.…”
Section: Ex Vivo Selectionmentioning
confidence: 99%